2020
DOI: 10.20961/agsjpa.v22i1.36007
|View full text |Cite
|
Sign up to set email alerts
|

Induksi Kalus Gaharu dengan NAA dan BAP Secara In Vitro

Abstract: <p>Agarwood has a high economic value because they have many benefits that cause agarwood to be hunted to meet the increasing market demand and its presence in nature is decreasing due to unwise conventional retrieval systems.The research objectives were to study the effect and determine the best concentration of NAA and BAP in callus induction of agarwood (Aquilaria malaccensis Lamk.). This research was conducted in the Tissue Culture Laboratory, Faculty of Agriculture, Andalas University from October 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
3
0
5
Order By: Relevance
“…Research Karyanti et al (2014) reported the addition of BA 1 mg/L in callus Jatropha curcas L. which was 10 weeks old produced 100% callus sprouts on solid media within 4 weeks after subculture. Furthermore, in the study of Karlianda et al (2010) and Wahyuni et al (2020) stated that the combination treatment of 0.1 mg/L NAA + 2.5 mg/L BAP was the best treatment that produced the highest number of shoots compared to other treatments in the agarwood callus subculture (Aquilaria malaccensis Lamk).…”
Section: Callus Developmentmentioning
confidence: 99%
“…Research Karyanti et al (2014) reported the addition of BA 1 mg/L in callus Jatropha curcas L. which was 10 weeks old produced 100% callus sprouts on solid media within 4 weeks after subculture. Furthermore, in the study of Karlianda et al (2010) and Wahyuni et al (2020) stated that the combination treatment of 0.1 mg/L NAA + 2.5 mg/L BAP was the best treatment that produced the highest number of shoots compared to other treatments in the agarwood callus subculture (Aquilaria malaccensis Lamk).…”
Section: Callus Developmentmentioning
confidence: 99%
“…Komposisi media yang tepat juga sangat berpengaruh terhadap biomassa kalus serta metabolit sekunder yang dihasilkan (Pono et al 2021). Faktor ketiga yang mendukung pertumbuhan eksplan adalah zat pengatur tumbuh (ZPT) (Wahyuni et al 2020). Zulkarnain (2011) menyatakan bahwa aplikasi ZPT sangat berpengaruh nyata dalam teknik kultur jaringan.…”
Section: Pendahuluanunclassified
“…Sejalan dengan pernyataan Widiyastuti (2015), pertumbuhan kalus ditandai dengan adanya pembengkakan dan terdapat jaringan berwarna putih kehijauan pada permukaan eksplan. Terbentuknya kalus disebabkan adanya rangsangan luka yang menyebabkan keseimbangan pada dinding sel berubah arah, sebagian protoplas mengalir ke luar sehingga mulai terbentuk kalus (Wahyuni et al 2020). Handoyowati (2016) menyatakan salah satu indikator adanya pertumbuhan dalam kultur jaringan adalah munculnya kalus pada eksplan.…”
Section: Waktu Muncul Kalusunclassified
See 2 more Smart Citations